Prevalence of Anemia and Vitamin B12 Deficiency in Children of Brick Kiln Workers, Aged Six to 59 Months: A Cross-Sectional Descriptive Study - Hanumante, Neeta; Narula, Arvinder Pal Singh; Deshpande, Aruna; Doke, Prakash Prabhakarrao (Indian Journal of Community Health, 2024)
Background: The brick kiln workers migrate with their families, which decreases health service utilization, leading to adverse effects on their children's health. Anemia studies on these children are scarce. Aim and Objectives: To estimate the prevalence of anemia and vitamin B12 in children of brick kiln workers. Methodology: It was a cross-sectional descriptive study. The study enrolled children aged 6–59 months from brick kilns. We took a detailed history and conducted a thorough physical examination. A blood sample was collected to estimate hemoglobin, Mean Corpuscular volume, Mean Corpuscular hemoglobin, Red Cell Distribution Width, serum ferritin, and vitamin B12 levels. Results: We assessed 90 children. The study observed that 61.1% of children had anemia (80.4% mild), mostly due to iron deficiency (94.5%). About 25% had vitamin B12 deficiency. All children with anemia were malnourished. Only age below 24 months, birth order ?2, and exclusive breastfeeding less than six months were significantly associated with anemia. There was no significant association between the demographic characteristics and Vitamin B12 deficiency. Conclusion: Iron deficiency anemia and B12 deficiency proportion among brick kiln workers’ children in was high. Hence, relevant community interventions to address the problem should be strengthened.